Skinner e o estudo do comportamento verbal pós 1957: alterações, complementos, reiterações e exclusões - Siracusa, Mariana Johansson (2018)
Amongst the basic concepts underlying the behavioral approach, the concept of verbal behavior is highlighted by Skinner in his book Verbal Behavior (1957). Taken into consideration that the studies about Skinner’s concept of verbal behavior have, for the most part, approached his path until the publication of Verbal Behavior, and that the studies about verbal behavior permeate throughout Skinner’s career, the present work aimed to analyze the evolution of Skinner's studies on verbal behavior after the publication of the book Verbal Behavior and pinpoint changes, complements, reiterations and possible exclusions. For that purpose, all of Skinner’s work published after 1957 containing the search words: verbal, language, mand, tact, echoic, copy, vocal, transcription, textual, intraverbal, autoclitic, audience, dictation, speaker, listener, oral, linguistics e self-management was analyzed; 282 entries from the Notebooks publication (1980) were also assessed. In all, there were 369 texts analyzed, from which 13 analytical categories were created, including the definition of verbal behavior; the definition of verbal operant; the definition and description of each one of the verbal operants: mand, echoic, textual, transcription, intraverbal and tact; the definition of audience; and four conceptual tools: discrimination and generalization, multiple causation of verbal behavior; definition and description of the autoclitic verbal operant; and self-control of verbal behavior. Complements were found in relation to the definitions of verbal behavior and verbal operants. Exclusions were found in the categories: Definition of Verbal Operant, Definition and Description of Verbal Operant Tanscription, and Definition and Description of Verbal Operant Tact. In the remaining categories, only reiterations were found. The results obtained by the present research make it possible to claim that Skinner made adjustments in the way he conceptualized verbal behavior throughout the publications investigated, in relation to what he had previously stated in his 1957 book